2010
DOI: 10.1097/jgp.0b013e3181c531fd
|View full text |Cite
|
Sign up to set email alerts
|

Can Persons With Dementia Be Engaged With Stimuli?

Abstract: Objectives To determine which stimuli are 1) most engaging 2) most often refused by nursing home residents with dementia, and 3) most appropriate for persons who are more difficult to engage with stimuli. Methods Participants were 193 residents of seven Maryland nursing homes. All participants had a diagnosis of dementia. Stimulus engagement was assessed by the Observational Measure of Engagement. Results The most engaging stimuli were one-on-one socializing with a research assistant, a real baby, personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 22 publications
4
48
0
2
Order By: Relevance
“…It would be interesting to examine other food-related interventions, such as cooking and dining NPIs, in future studies. Second, we saw that 1-on-1 socializing was relatively barrier-free, concurring with prior research that found less refusal and more engagement with live 1-on-1 social contact 38 . Third, NPIs not needing active participation by the resident (e.g., movies) were linked with fewer barriers than those requiring active participation (e.g., puzzles).…”
Section: Discussionsupporting
confidence: 88%
“…It would be interesting to examine other food-related interventions, such as cooking and dining NPIs, in future studies. Second, we saw that 1-on-1 socializing was relatively barrier-free, concurring with prior research that found less refusal and more engagement with live 1-on-1 social contact 38 . Third, NPIs not needing active participation by the resident (e.g., movies) were linked with fewer barriers than those requiring active participation (e.g., puzzles).…”
Section: Discussionsupporting
confidence: 88%
“…The high refusal rates of robotic animals and real looking dolls may be related to their low social acceptability(26). To better ascertain the factors that affect refusals, future research should control for interventions` social value and appropriateness, the amount of involvement required, and the cognitive level of participants.…”
Section: Discussionmentioning
confidence: 99%
“…While those stimuli have been shown to engage persons with dementia (Cohen-Mansfield et al, 2010) and thus may be useful activities for persons with dementia who are unable to engage themselves, those stimulus categories do not seem beneficial for enhancing positive affect in this population.…”
Section: Discussionmentioning
confidence: 99%